2000
DOI: 10.1046/j.1460-9568.2000.00249.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of sst2 somatostatin receptor in locomotor, exploratory activity and emotional reactivity in mice

Abstract: Somatostatin (SRIF) controls many physiological and pathological processes in the central nervous system but the respective roles of the five receptor isotypes (sst1–5) that mediate its effects are yet to be defined. In the present study, we attempted to identify functions of the sst2 receptor using mice with no functional copy of this gene (sst2 KO mice). In contrast with control 129Sv/C57Bl6 mice, sst2 mRNA was no longer detectable in the brain of sst2 KO mice; 125I‐labeled Tyr0DTrp8‐SRIF14 binding was also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
60
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(70 citation statements)
references
References 45 publications
7
60
1
2
Order By: Relevance
“…In this study, we demonstrate that elevation in glucocorticoid levels in the Sst Ϫ/Ϫ mouse are associated with a significant increase in pituitary POMC expression, without a concomitant rise in hypothalamic CRH expression. These in vivo results, coupled with our present in vitro findings showing that SST can directly suppress POMC mRNA levels and ACTH release in primary mouse pituitary cell cultures and with the fact that pituitaries of sst2 knockout mice release more ACTH in vitro (47), strongly support the hypothesis that, at least in the mouse, endogenous SST can act as a corticotropin synthesis/release-inhibiting factor (14). The fact that the direct inhibitory actions of SST on POMC mRNA levels and ACTH release were also observed in primary pituitary cell cultures from a nonhuman primate suggests that endogenous SST may also play an important role in regulating corticotroph function in higher-order mammalian species, such as humans.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In this study, we demonstrate that elevation in glucocorticoid levels in the Sst Ϫ/Ϫ mouse are associated with a significant increase in pituitary POMC expression, without a concomitant rise in hypothalamic CRH expression. These in vivo results, coupled with our present in vitro findings showing that SST can directly suppress POMC mRNA levels and ACTH release in primary mouse pituitary cell cultures and with the fact that pituitaries of sst2 knockout mice release more ACTH in vitro (47), strongly support the hypothesis that, at least in the mouse, endogenous SST can act as a corticotropin synthesis/release-inhibiting factor (14). The fact that the direct inhibitory actions of SST on POMC mRNA levels and ACTH release were also observed in primary pituitary cell cultures from a nonhuman primate suggests that endogenous SST may also play an important role in regulating corticotroph function in higher-order mammalian species, such as humans.…”
Section: Discussionsupporting
confidence: 82%
“…The inhibitory action of exogenous SST on ACTH release has prompted speculation regarding the role of endogenous SST as a corticotropin release-inhibiting factor (14). More recent observations support such a role, where pituitaries of sst2 knockout mice release more ACTH in vitro (47) and corticosterone levels are elevated in SST knockout mice (Sst Ϫ/Ϫ ) (50). Preliminary data generated by our laboratory have confirmed that basal corticosterone levels are elevated in both male and female Sst Ϫ/Ϫ mice (28).…”
mentioning
confidence: 99%
“…We used four strains of mice in this study: somatostatin receptor subtype 2 (SST 2 ) knock-outs, SST 3 knock-outs, SST 4 knock-outs, and wild-type mice. SST 2 knock-out mice were provided by Merck Pharmaceuticals (Whitehouse Station, NJ) and have been characterized phenotypically (Viollet et al, 2000;Dutar et al, 2002). We did limited studies on SST 2 / SST 4 double knock-outs, which were bigenic crosses between the SST 2 and SST 4 knock-outs.…”
Section: Methodsmentioning
confidence: 99%
“…for sst1 -sst4 (18) and for sst5 (19)) but the most studied remain sst2 and sst5 KO mice. The studies of sst2 gene KO mice indicated that this receptor displays specific central actions such as fine motor control (20), modulation of spatial learning (21), exploratory activity and emotional reactivity (22). Among the peripheral actions of SRIF, sst2 receptor appears specifically involved in the inhibition of gastric acid secretion (23,24).…”
Section: Somatostatin (Sst) Receptor Familymentioning
confidence: 99%